Detektor Anomali Jaringan dengan Analisis Perilaku untuk Mengidentifikasi Ancaman Persisten - Rakhmadi Rahman; Andi Maharani; Nur Azisah Basir (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Technological developments in the digital world have now begun to increase the use of operating systems such as Android which are often used on electronic devices such as smartphones and tablets, penetrating various fields of human life. The use of these devices is essential in facilitating various tasks, especially digital ordering and transactions. This integration provides better transaction protection, more effective usage, and benefits and convenience. Cloud computing makes it easy and efficient to integrate digital ordering applications into payment systems. Observations show that these integrations provide user convenience and purchase trends, assist marketing strategies, and generate more accurate business decisions. If carefully developed and implemented, this integration has great potential to change the way business is done in the digital age.